1998
DOI: 10.1021/ja972550b
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the Absolute Configuration of β-Chiral Primary Alcohols by NMR:  Scope and Limitations

Abstract: The prediction of the absolute configuration of β-chiral primary alcohols from the 1H NMR spectra of their esters with (R)- and (S)-9-anthrylmethoxyacetic acids (9-AMA, 3) is discussed. Low-temperature NMR experiments, MM, semiempirical, ab initio, and aromatic shielding effect calculations allowed the identification of the main conformers and showed that, in all alcohols for which the calculated ΔE ag (CVff) is in the range of 0.7−1.5 kcal/mol, conformer a / a is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 31 publications
1
65
0
Order By: Relevance
“…In the present study, we examined the relation between the absolute configuration and oxymethylene proton chemical shifts in the MTPA esters of simple primary alcohols (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) with a C2-branched methyl. Like the case of compounds 1-7, if the differences between Dd S and Dd R are relatively large (Ͼ0.10 ppm) they allow the assignment of the absolute configurations at the oxymethine carbons at C2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we examined the relation between the absolute configuration and oxymethylene proton chemical shifts in the MTPA esters of simple primary alcohols (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) with a C2-branched methyl. Like the case of compounds 1-7, if the differences between Dd S and Dd R are relatively large (Ͼ0.10 ppm) they allow the assignment of the absolute configurations at the oxymethine carbons at C2.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is difficult to assign the absolute configurations of tertiary and primary alcohols since of the irregular arrangements of the Dd values. 1,4) Although attempts to assign the absolute stereochemistry of C2-chiral primary alcohols using its MTPA esters have been demonstrated, there is no conventional method applicable for a limited amount of natural products. 5) Minale and coworkers have applied a Mosher's method for determination of absolute stereochemistry of a methyl group at C25 of steroids with a primary hydroxyl group at C26, 6,7) and reported that the proton signals of the methylene (C26) attached to the ester linkage in the MTPA derivatives showed a unique split pattern as follows.…”
mentioning
confidence: 99%
“…Though several methods for asymmetric carboxylic acid preparations are highly reliable in effecting predictable stereochemical outcomes, each synthesis requires an independent confirmation of the product configuration and purity. Proton NMR, in particular, has been widely employed to provide dependable assignments for carboxylic acids, [3][4][5][6][7] alcohols, 8,9 and amines [10][11][12][13][14] covalently bound to chiral derivatizing agents (CDAs). In this report we describe the determination of the absolute configuration of chiral acids via proton NMR analysis of their conjugates with known dihydropyrimidinone 1.…”
Section: Introductionmentioning
confidence: 99%
“…A series of diastereomeric conjugates of 1 were prepared to examine the effect of carboxylic acid structure on the proton NMR shifts patterns ( Table 2). The analogs were designed to examine the influence of the size of the alkyl group (4 and 5), the presence of a heteroatom attached to the chiral center (6), and the size of the aryl group (7 and 8) or its absence (12)(13)(14). In addition, other samples were prepared to investigate combinations of structural influences (9) or commercially important applications (10 and 11).…”
Section: Introductionmentioning
confidence: 99%
“…2). 5) Thus, the absolute stereochemistry of compound 2 was determined and was found to possess 2S configuration. The 2S configuration was confirmed by the fact that the specific optical rotation of compound 2 was ϩ38.5, whilst the specific optical rotation of (R)-phenyl-1,2-ethanediol was Ϫ58.0 under the same test condition.…”
mentioning
confidence: 99%